(untitled) (AYUSHDHARA, 2025)
Vaasathi Kashayam, a Siddha herbal decoction from Agathiyar 2000, is formulated using Adhathoda vasica (Justicia adhatoda L.) leaves and dry grapes (Vitis vinifera L.). This study evaluates its anti-hypertensive, antioxidant, and diuretic effects. Methodology: DOCA-salt-induced hypertensive Wistar albino rats (5 groups, n=6) were treated for 43 days. Blood pressure (BP), serum sodium, and potassium levels were measured. Blood was collected via retro-orbital plexus under ether anesthesia; BP was recorded through cannulated carotid artery using the 2K1C model. Diuretic effect was assessed using 4 groups (n=6) in metabolic cages, measuring total urine volume and Na⁺, K⁺, Cl⁻ levels. Cl⁻ was estimated as NaCl by titration. Antioxidant activity was assessed via DPPH free radical scavenging assay. Acute and subacute toxicity studies followed OECD 423 guidelines. Results: Hypertensive rats had SBP/DBP of 173.33±2.33/145.54±1.23mmHg. Low-dose (200mg/kg) Vaasathi Kashayam reduced BP to 135.03±2.56/92.63±1.01 mmHg, and high-dose (400 mg/kg) to 106.02±3.46/ 72.05±0.53mmHg, comparable to the standard (hydrochlorothiazide) 103.72±1.25/ 92.63±1.82mmHg. Diuretic activity showed increased urine output (32.53±0.83 and 30.67±0.06mL) and elevated urinary electrolytes, comparable to Furosemide. Antioxidant activity peaked at 63.15% inhibition (300µg/mL); standard ascorbic acid showed 132.06% inhibition. No significant toxicity or abnormal changes were observed in acute (up to 2000mg/kg) or subacute (28-day) studies. Conclusion: Vaasathi Kashayam is a safe formulation with significant anti-hypertensive, antioxidant, and diuretic activities, supporting its therapeutic potential in Siddha medicine.